VALIDITY OF SCIENCE LEARNING DEVICES WITH CASE-BASED LEARNING MODEL ASSISTED BY PHET MEDIA - Astutik, Fitriyah Ika; Holida, Ida (Jurnal Konseling Pendidikan Islam, 2025)
The purpose of this study is to test the level of validity of developing learning devices with the CBL model assisted by PhET media. The method used is the research and development method. The results of the initial study show that the critical thinking ability of students at Waru Barat 4 State Elementary School in Pamekasan in science subjects is still low, as evidenced by students' difficulty in analyzing. HOTS questions are given by teachers because the learning activities carried out at school tend to be rote learning. Therefore, the researcher developed a CBL learning tool with the help of PhET media which includes lesson plans, teaching modules, student activity sheets, assessment sheets, and textbooks that can improve students' critical thinking skills. The purpose of this study was to obtain a valid learning tool. Based on the results of the validity test conducted with three education experts, it was found that the learning tool developed met the valid category so that it could be implemented to improve the critical thinking skills of elementary school students.